Lymph node characteristics of sarcoidosis with endobronchial ultrasound - Ozgul, Mehmet Akif; Cetinkaya, Erdogan; Kirkil, Gamze; Ozgul, Guler; Abul, Yasin; Acat, Murat; Dincer, H. Erhan (Lippincott Williams & Wilkins, 2014)
Background: Sonographic features of lymph nodes on endobronchial ultrasound (EBUS) have been shown to be useful in prediction of malignancy in mediastinum and hilum. The aim of this study was to assess the utility of morphologic features of mediastinal and/or hilar lymph nodes obtained by EBUS in patients with sarcoidosis. Materials and Methods: We retrospectively reviewed the records of 224 patients with mediastinal/hilar lymph node enlargements who underwent EBUS for diagnostic purpose. The lymph nodes were characterized based on the EBUS images as follows: (1) Size; based on short-axis dimension, <1 cm or >= 1 cm, (2) shape; oval or round, (3) margin; distinct or indistinct, (4) echogenicity; homogeneous or heterogeneous, (5) presence or absence of central hilar structure, and (6) presence or absence of granular (sandpaper) appearance. Results: One hundred (24.4%) nodes exhibited indistinct margins while 309 (75.6%) had distinct margins. One hundred and ninety nine (48.7%) nodes were characterized as homogeneous, and 210 (51.3%) nodes as heterogeneous. Granular appearance was observed in 130 (31.8%) lymph nodes. The presence of granules in lymph nodes on EBUS had the highest specificity (99.3%) for the diagnosis of sarcoidosis. Logistic regression analysis revealed the finding of distinct margin alone as an independent predictive factor for the diagnosis of sarcoidosis. Conclusions: The presence of granular appearance in lymph nodes by EBUS had the highest specificity (99.3%) for the diagnosis of sarcoidosis. Lymph nodes having distinct margins tend to suggest sarcoidosis.
Keywords: Diagnosis; echoic features; endobronchial ultrasonography; sarcoidosis